Analysis of Mammograms Performed in a Public Imaging Center in Santiago, Metropolitan Region Chile 2008-2018 [Estudios Mamográficos en Un Centro Metropolitano de Referencia en Imágenes Mamarias: Chile 2008-2018 ¿Vamos por el Camino Correcto?] - Vega-Fuentes, N (Sociedad Medica de Santiago, 2022)
Background: Mammograms are one of the most effective preventive means for the early detection of breast cancer. Objective: To describe the features of patients and results of mammograms performed at a public breast imaging service of the Santiago Metropolitan Area. Material and Methods: We reviewed the reports of mammograms performed on 174, 017 women and 18 men, between 2008 and 2018 in an Imaging Center. The BI-RADS classification was used in the reports. Results: Forty-six percent of mammograms (75, 781) were reported as BI-RADS 2. The high proportion of BI-RADS 4 reports (674 reports) was seen in patients aged 40 to 49 years, corresponding to 30% of reports in this age range. Among patients aged 50 to 59 years, there were 779 BI-RADS 4 reports (35%). BI-RADS 5 reports were more common among patients aged 50 to 59 years (50 reports, 30%) and among patients aged 70 years or older (83 reports, 28%). Conclusions: The presence of a significant number of women between 40 and 49 years of age with a BI-RADS 4 mammography result stands out; being an opportunity to develop new clinical research and public health strategies within the framework of the Universal Health Care policy for breast cancer in Chile. © 2022 Sociedad Medica de Santiago. All rights reserved.